Stabilisation of self-assembled DNA crystals by triplex-directed photo-cross-linking. Issue 51 (6th June 2016) - Abdallah, Hatem O.; Ohayon, Yoel P.; Chandrasekaran, Arun Richard; Sha, Ruojie; Fox, Keith R.; Brown, Tom; Rusling, David A.; Mao, Chengde; Seeman, Nadrian C.
Abstract : Cross-linked crystals: triplex-forming oligonucleotides can direct cross-linking reactions within or between tiles of a DNA crystal, improving their thermal stability. Abstract : The tensegrity triangle is a robust DNA motif that can self-assemble to generate macroscopic three-dimensional crystals. However, the stability of these crystals is dependent on the high ionic conditions used for crystal growth. Here we demonstrate that a triplex-forming oligonucleotide can be used to direct the specific intercalation, and subsequent photo-cross-linking, of 4, 5′, 8-trimethylpsoralen to single or multiple loci within or between the tiles of the crystal. Cross-linking between the tiles of the crystal improves their thermal stability. Such an approach is likely to facilitate the removal of crystals from their mother liquor and may prove useful for applications that require greater crystal stability.